Study on Underground Utility Tunnel Fire Characteristics under Sealing and Ventilation Conditions - Hongtao Zhang; Yufei Zhao (Advances in Civil Engineering, 2020)
With the development of the underground utility tunnel in China, the safety evaluation during facility operation inside tunnels is increasingly important after construction. In contrast to fixed fire source in the traffic tunnel, the fire characteristics of the electric cable compartment of the utility tunnel with different ventilation modes are studied. Firstly, the thermal physical parameters of cable material are determined by experiment and numerical simulation. Different fire sealing and ventilation conditions are established according to the practical utility tunnel engineering in FDS. The maximum temperature and smoke gas concentrations are obtained, as well as the heat release rate. The results show that the utility tunnel fire has obvious differences compared with road tunnel fire, where the maximum ceiling temperature and the distributions of smoke is related to fire sealing and ventilation mode. Some suggestions related to evaluation and firefighting are provided for practical purposes.